Adaptive Agents and Multi-Agent Systems II Adaptation and Multi-Agent Learning - Kudenko, Daniel; Kazakov, Dimitar; Alonso, Eduardo (Lecture Notes in Artificial Intelligence,, 2005)
Adaptive agents and multi-agent systems is an emerging and exciting interdisciplinary area of research and development involving artificial intelligence, software engineering, and developmental biology, as well as cognitive and social science. This book presents 17 revised and carefully reviewed papers taken from two workshops on the topic as well as 2 invited papers by leading researchers in the area. The papers deal with various aspects of machine learning, adaptation, and evolution in the context of agent systems and autonomous agents.